2010
DOI: 10.1007/s11274-010-0341-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and evaluation of significant mycoflora and mycotoxins in pig feed from Serbian farms

Abstract: This paper provides a brief review of approaches for the early detection and prevention strategies which have been employed in Serbia for the control of ochratoxogenic fungi and its metabolites in feed in the context of a hazard analysis critical control point (HACCP) framework. During a mycological analysis of complete feedmixes intended for fattening swine (n = 18), a total of six genera and 14 species of moulds were identified. Penicillium was present in considerably more samples than any other genus (94.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Analogous to our results, Milićević et al (2010) have established total fungal count ranging from 1 × 10 5 to 40 × 10 5 cfu g -1 in 18 pig feed samples collected from different provinces in Serbia, of which 39% samples exceeded the limit according to the Serbian legislation. They have also reported that with the storage period of pig feed extending, the moisture content is increasing.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Analogous to our results, Milićević et al (2010) have established total fungal count ranging from 1 × 10 5 to 40 × 10 5 cfu g -1 in 18 pig feed samples collected from different provinces in Serbia, of which 39% samples exceeded the limit according to the Serbian legislation. They have also reported that with the storage period of pig feed extending, the moisture content is increasing.…”
Section: Resultssupporting
confidence: 89%
“…In addition to potentially toxigenic fungi from Fusarium, Aspergillus and Penicillium genera, Alternaria, Mucor and Rhizopus species were also identified but in a small percentage of examined samples (data not presented). Milićević et al (2010) registered the most number of pig feed samples contaminated with Penicillium species (94.4%). Fusarium species were present in 55.5% and Aspergillus species in 22% of pig feed samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, in another study, the consumption of AFB1 did not affect the dry matter intake or milk yield, however, it tended to reduce the FCM, milk fat production and milk protein concentration [ 34 ]. A diverse diet (including several types of feedstuffs, usually) and a large body mass may help dairy cows to resist mycotoxins [ 33 , 35 ]. The small amounts of mycotoxins consumed in the present study compared with the high overall feed intake may have ensured that the dilution effect rendered them relatively harmless [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on the prevalence of OTA producing species in Serbia are scarce and limited to a small number of studies [84,96]. Next, to the cereals and other insufficiently dried commodities, OTA has been detected in pig’s blood, kidney, liver muscle and adipose tissue with rather high levels found in animals suffering from porcine nephropathy, especially in countries of the Balkan Peninsula [33].…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%